Continuous assesment as a mediating variable between class attendance and students’ performance / Nur Hidayah Md Noh ... [et al.] - Md Noh, Nur Hidayah; Hassanuddin, Nor Aini; Yusoff, Sarah; Mohamad Sukri, Nursyazni (2018)
In higher education, besides final examination, students’ performance will also be measured throughout 14 weeks of lecture that contains tests, projects, quizzes and assignments as their continuous assessment. In UiTM, the continuous assessment for statistical subject is in range of 40% to 60% that contributes to their performance. This percentage is considered high and students cannot neglect this factor if they want to get good grades. With this belief, the effect of continuous assessment as mediating variable to determine relationship between final examination performance and students’ classroom participation throughout one semester in UiTM Kuala Terengganu among Diploma of Computer Science (CS110) students and Bachelor of Business Computing (CS244) students from Faculty of Computer Science and Mathematics who undertook a statistics course will be studied. Positive correlation was reported indicating that there exists positive relationship between classroom attendance and final examination grades. Students then were grouped into two groups according to the ‘80% rule’. Furthermore, Sobel Test indicates that there exists mediating effect of continuous assessment between class attendance and final mark. As a conclusion, participation and understanding the lecture in a statistics class is an important indicator that contributes to their performance.